KEEFEKTIFAN NORTH ATLANTIC TREATY ORGANIZATION (NATO) MEMIMPIN INTERNATIONAL SECURITY ASSISTANCE FORCE (ISAF) DI AFGHANISTAN TAHUN 2002-2012 - Susanti, Anis; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper explains about the effectiveness of the North Atlantic Treaty Organization (NATO) led the International Security Assistance Force (ISAF) in Afghanistan in 2002-2012. NATO is an international organization that emphasizes the military defense sector in the countries of the North Atlantic. While ISAF is an inter-state cooperation that aims to make the program successful reconstruction of Afghanistan. This paper begins by explaining what is being done mission ISAF in Afghanistan, the first mission is done ISAF mission for security, reconstruction and construction of the second and the third rule. Mission most emphasized by ISAF in Afghanistan is security, because of the threat of the Taliban to Afghanistan, as well as the spread of narcotics. That is why Afghanistan had help from NATO. However, whether effective or not assistance is done through NATO ISAF to Afghanistan?.In fact, the research concluded that the program performed the NATO-led ISAF to help Afghanistan is not effective, or can be said to have not been successful, because we can see the current state of Afghanistan, they are still not ready to face the threats of the enemy, in Afghanistan there are still many the spread of narcotics, it indicates that the NATO program for about twelve years of the leadership of Hamid Karzai is still not much change.Keywords: security, threat, ISAF program effectiveness, government of Hamid Karzai.